STRUKTURALISME DALAM LIRIK LAGU “NOT LIKE THE MOVIE” KATTY PERY - Lida, Ulfah Mey (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2019)
The song is a work of art that comes from the relationship of sound and language. The purpose of this research is to know the structuralism in Katty Pery's song "Not Like The Movie" lyrics. This research is a qualitative research with analysis model from Miles and Huberman. The results of this study are Each word used in the lyrics of the song are interconnected with each other (sintagmatic). The paradigmatic chain (vertically) is derived from the word selection association which refers to the relation of meaning between one word to another that can be exchanged. The image of the sound that emerged (signifiant) in the fragment of the song lyrics above is very beautiful. The acceptable impression of meaning that the "I" character in the lyrics of the song was shocked and depressed when he heard bad news about the man who meant so much to him.